TRANSPLANTATION IN CHILDREN AND ADOLESCENTS - Ana Gianini; Simona Ivančan; Kaja Podlogar; Magda Zupan; Uroš Krivec; Erika Šmid; Sanja Borčić; Simona Kotar Grandovec; Slavica Popovič; Anita Štih (The Society for Children with Metabolic Disorders, 2024)
Transplantation in children and adolescents is a highly complex treatment method. The nurse's active involvement in the multidisciplinary team's work contributes to a higher quality of patient care. Good multidisciplinary cooperation can reduce the frequency of potential complications can be reduced and hospitalization duration shortened. Patients often face fear and social isolation. Additional difficulties arise due to the underlying disease complicating or worsening the health condition. The nurse also plays a significant role in health education. Health education typically begins during the patient's preparation for transplantation or when the patient is placed on the waiting list. As a rule, medical education begins already during the preparation of the patient for transplantation or when the patient is placed on the waiting list. Patients and parents must receive comprehensive and truthful information for favourable treatment outcomes.